Milk Production, Consumption and Digestibility of Ration Based on The Palm Kernel Cake, Tithonia (Tithonia Diversifolia) and Corn Waste on Etawa Crossbreed Dairy Goat. Issue 1 (March 2021) - Arief,; Rusdimansyah,; Sowmen, S; Pazla, R
Abstract: This study aims to evaluate milk production, consumption and digestibility of rations in Etawa Crossbreed Dairy Goats (ECDG) fed with concentrate of palm kernel cake (CPKC), tithonia (Tithonia diversifolia) and corn waste. The design used was a completely randomized design with 4 treatment rations and 5 replications. Treatment A = 7.5 kg titonia + 4 kg tofu waste, B = 7.5 kg tithonia + 2 kg tofu waste + 1.2 kg CPKC, C = 2 kg corn waste + 5.5 kg tithonia + 2 kg tofu waste + 1.2 kg of CPKC, D = 4 kg of corn waste + 3.5 kg of tithonia + 2 kg of tofu waste + 1.2 kg of CPKC. Data were analyzed by ANOVA and DMRT as further tests. The parameters measured were milk production, consumption and digestibility of the ration. The results showed that the treatment had an insignificant different effect (P> 0.05) on milk production, ration consumption and digestibility. The conclusion of this study is the use of CPKC, tithonia and corn waste able to maintain milk production, consumption and digestibility ration.